The Role of Dynamic Computed Tomography Angiography in Endoleak Detection and Classification After Endovascular Aneurysm Repair: A Comprehensive Review - Alexandra Catasta; Claudio Bianchini Massoni; Davide Esposito; Sara Seitun; Giovanni Pratesi; Nicola Cicala; Antonio Freyrie; Paolo Perini (Diagnostics)
Backgroud: The use of dynamic computed tomography angiography (dCTA) for the detection of endoleaks in patients who underwent endovascular repair of abdominal aortic aneurysms is gaining interest. This study aims to provide an overview of the current applications of dCTA technologies in vascular surgery. Methods: We performed a comprehensive review by searching in the PubMed database and Cochrane Library (last search: 1 November 2024). We included studies considering endoleak investigation after endovascular aneurysm repair (EVAR). We included papers that reported the outcome of applications of dCTA, excluding case reports or very limited case series (≤4). Finally, 14 studies regarding 377 computed tomography angiographies (CTA) were included and evaluated. Results: Persistent perfusion of the aneurysm sac is the most common complication after EVAR. Imaging-based surveillance post-EVAR is essential with the aim of early detection, characterization, and localization of endoleaks to guide therapeutic intervention or follow-up. dCTA detected 36 type I endoleaks versus 16 identified with standard CTA and 138 versus 95 type II endoleaks. Conclusions: The emergence of dCTA offers a promising solution through enhanced temporal resolution, allowing the visualization of real-time flow dynamics within the aneurysmal sac essential to establishing endoleak treatment or post-EVAR follow-up.